Evaluation of immediate loading of single dental implants in the maxillary esthetic zone: Clinical and radio graphical comparative study - Al Naqshabandi, Serwan Saeb; Omar, Othman Abubakir (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Loading an implant right after placement has been attempted and has gained popularity among clinicians. The aim of this study was to evaluate the clinical and radiographical outcomes of immediate loading of single dental implant placed in healed and in fresh extraction sockets. Methods: In a prospective, comparative, clinical study, 40 patients underwent single dental implant procedure in the maxillary esthetic zone. Twenty implants were placed into fresh extraction sockets (Group A), and the other 20 implants were placed into healed extraction sockets (Group B). Placement of the permanent crown was done within two weeks after implant placement. Results: From a total of 40 implants only two failed to survive giving a cumulative survival rate of 95%. Both failures occurred in fresh extraction sockets resulting in a survival rate of 90%, while no implant failed in healed sites achieving 100% survival rate. The difference in marginal bone loss between two groups was statistically significant. Conclusion: The immediate loading of single dental implant in maxillary esthetic zone is a viable clinical concept and lead to favorable treatment outcomes.